(untitled) (Global Journal of Management and Business Research, 2016)
This paper discusses internal complexity of assets and option pricing. We review the Black-Scholes-Merton equation within economic space point of view. We argue reasons for economic space definition and discuss it’s application for options pricing. Our approach allows revise classical Black-Sholes-Merton model and discovers hidden complication for truthful pricing of assets and options. We derive Black-Sholes-Merton equation on n-dimensional economic space and argue tough problems that should be solved to make option pricing more accurate.